The manifestations of Islamic religious architecture in artistic paintings-For students of art education (The Peerian Journal, 2023)
The world is decorated with aspects of architecture, and this is what extends to the Islamic environment, as the Muslim architect innovated in the field of architecture with a group of religious architectural objects and formulated them in a style that blends the spirit of aesthetics, simplicity, and beliefs after being confused by the issue of the limits of accepting the art of photography. In the Islamic environment, and with logical, scientific curiosity, the current research aims to identify the aspects of Islamic religious architecture embodied in project paintings for fourth-grade students in the Department of Education. To achieve the goal of the research, the researcher built an analysis form from (3) areas, and after verifying the validity and reliability of the tool, it was applied to ( 22) One of the graduation project paintings. The researcher found that the field of function, the field of function and aesthetics, and the field of decoration appeared at a rate of (77%), (63%), and (68%), respectively, meaning that aspects of architecture in general appeared at a level of more than half in project drawings. Fourth grade students